If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5.1 = -4u + 17.9 Reorder the terms: 5.1 = 17.9 + -4u Solving 5.1 = 17.9 + -4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '4u' to each side of the equation. 5.1 + 4u = 17.9 + -4u + 4u Combine like terms: -4u + 4u = 0 5.1 + 4u = 17.9 + 0 5.1 + 4u = 17.9 Add '-5.1' to each side of the equation. 5.1 + -5.1 + 4u = 17.9 + -5.1 Combine like terms: 5.1 + -5.1 = 0.0 0.0 + 4u = 17.9 + -5.1 4u = 17.9 + -5.1 Combine like terms: 17.9 + -5.1 = 12.8 4u = 12.8 Divide each side by '4'. u = 3.2 Simplifying u = 3.2
| y^3+16y-y^2-16=0 | | [6-(-8)]-8= | | 7.2=y+(-1.5) | | -(1+0.3r)=-13+7.7r | | 7y=5y(y+2) | | 5x+8-6x+7=112 | | -1.3+(w/2)=-26.9 | | =2cd | | (x+4)(x^2+4x+16)=0 | | -3/7x=3 | | 6(x-1)+4=3x+3(-2+x) | | 9x-23-5x+20=1 | | 16-|-4+6|= | | -3y=-22.5 | | 2a/2 | | 2a+b=115.7 | | 2x^2+(x^2y-2xy^2)= | | 2x/x-2+x/x+3=-5/x+3 | | 5.5=-2+y | | 3/4k+2 | | 150=x+15+3x+1 | | 27x+12=4(6x+2)+3x+4 | | 6a=4a | | -3(pie)+w=2(pie) | | (2x)/(x-2)+(x)/(x+3)=(-5)/(x+3) | | -96=4y | | |3-5|+13= | | 48=x-3+2x+10 | | (4(x-1)/6)=(2(x+1)/5) | | x=2/3y | | 3x+4-x=2+x+1 | | 3u+8=56 |